anonymous
  • anonymous
how do i solve x2 – 2x = 8 by completing the square?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
\[(x-1)^2=8+1=9\] \[x-1=\pm3\] \[x-1=3\implies x=4\] \[x-1=-3\implies x=-2\]
anonymous
  • anonymous
i need to show the work, can you explain how you got this?
anonymous
  • anonymous
Could you @satelite try to answer my question

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Ummm
anonymous
  • anonymous
We generally don't complete the square to solve for a variable. We usually use it to place a quadratic equation into vertex form in order to graph or solve a word problem. \[x ^{2}-2x=8\] Bring everything to one side \[x ^{2}-2x-8=0\] Now we place brackets around the first two terms: \[(x ^{2}-2x)-8=0\] Now we need to create a nice perfect square in the brackets. We do this by taking half of x's coefficient and squaring it. In this case (2/2)^2 = 1 We then add and subtract this number, thereby not "really" changing the equation. \[(x ^{2}-2x+1-1)-8=0\] We bring the subtracted term out of the brackets: \[(x ^{2}-2x+1)-1-8=0\] Then we factor the bracket: \[(x-1)^{2}-1-8=0\] Simplify: \[(x-1)^{2}-9=0\] That would be vertex form (if the 0 was a y) So if we want to solve: \[(x-1)^{2}=9\] Square root both sides, this actually gives us a plus and minus version: \[x-1= +/-3\] so we have two solutions: \[x=-2\] and \[x=4\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.